Aerial view of Vaux, south of Chateau-Thierry - Gordon, John C. (photographer):::Creator::::::::::::
Aerial view of the damaged village of Vaux, France, after the Battle of Chateau-Thierry in World War I. The caption at the lower left of the photograph reads "Vaux- south of Chateau-Thierry.. [illegible] 1918." The Battle took place on July 18, 1918.